Competitive Market Structures: A Subset Selection Analysis - Kannan, P. K.; Sanchez, Susan M. (Management Science, 1994)
Market structure models are used to identify submarkets or to test for the presence of submarkets where within-group competition is much stronger than across group competition. The implicit assumption in such models is that the brands in a submarket compete on the basis of their shared product features. However, if significant variety-seeking effect exist in the market, such an assumption may not be valid. We present a model based on a subset selection procedure for analyzing competitive market structures and develop tests of significance for variety-seeking effects present in the market. For each brand in the market, the subset selection procedure identifies sets (submarkets) of brands that are in “close” competition. The competitive market structure is defined by the possibly overlapping submarkets that are identified for each brand and the model provides insights on whether the brands in a submarket are of a reinforcing or a variety-seeking kind. The application of our model to two different consumer packaged goods markets highlights its contribution relative to extant methods.